2021
DOI: 10.4300/jgme-d-20-00642.1
|View full text |Cite
|
Sign up to set email alerts
|

Automated Procedure Logs for Cardiology Fellows: A New Training Paradigm in the Era of Electronic Health Records

Abstract: Background Procedural experience for residents and fellows is critical for achieving competence, and documentation of procedures performed is required. Procedure logs serve as the record of this experience, but are commonly generated manually, require substantial administrative effort, and cannot be corroborated for accuracy. Objective We developed and implemented a structured clinical-educational report template (CERT), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Researchers consistently showed that manual procedure logging was markedly incomplete, inaccurate, or both when compared with EHR-derived logs. All articles that compared EHR-measured procedures with manual logs demonstrated incomplete capture (5 of 5 [100%]), with manual logs capturing between 50% and 76% of procedures performed, 23,25,26,28,30 despite efforts to improve manual logging through targeted reminders. 28 Three studies compared the accuracy of manually entered procedure codes with EHR codes, with rates ranging from 47% to 87%.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers consistently showed that manual procedure logging was markedly incomplete, inaccurate, or both when compared with EHR-derived logs. All articles that compared EHR-measured procedures with manual logs demonstrated incomplete capture (5 of 5 [100%]), with manual logs capturing between 50% and 76% of procedures performed, 23,25,26,28,30 despite efforts to improve manual logging through targeted reminders. 28 Three studies compared the accuracy of manually entered procedure codes with EHR codes, with rates ranging from 47% to 87%.…”
Section: Resultsmentioning
confidence: 99%
“…Fellows self-reported femoral CVC placement attempts in MedHub which may lead to both underreporting and potential inaccuracy in the date the procedure was performed. 36 37 We did not include CVC placement attempts at other anatomic sites in our study, which likely provided additional opportunities for experiential learning in shared aspects of the procedure. HMA measurements were performed during CVC placement on a simulation task trainer rather than on actual patients, which likely led to higher levels of performance given the relatively larger vessel size and controlled environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one approach was described in which the metadata needed to link a procedure were added to the documentation completed by cardiology fellows. 12 This type of approach could be expanded to record trainee involvement in a standardized way, but a concern to be addressed is the inclusion of non-clinical data (eg, the specific role of trainees involved in a case) to clinical notes.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,11 Past studies identified multiple factors that resulted in increased administrative time for residents, including the ambiguity in categorizing a surgery into multiple component procedures and determining resident role for a case. 2,5 Other work has proposed automated procedure logs or clinical registries to reduce manual documentation, 12,13 but these approaches have not addressed a key issue-linking a procedure to a trainee and then transmitting the data to the ACGME. The difficulty to determine from the electronic health record (EHR) which cases are performed by a resident surgeon also makes it challenging to assess resident case log initiatives.…”
Section: Introductionmentioning
confidence: 99%